Research On Supply Chains Within The Power Energy Sector: Salient Points In A Pandemic Situation - Eleonora HARSAN (Communications of International Proceedings, 2021)
The main objective of this paper is to highlight the salient points within the power energy supply chain in the context of the pandemic crisis. Intention is to achieve a desk-study article research which may be developed later as part of a PhD thesis. Generally for the supply chains  topic there is a large reference list from professional associations, furthermore the hot topic of supply chains in pandemic came frequently in the titles of many  international consulting groups and publishers last year. Methodology research is based on an empirical study of existing literature complemented by an comprehensible analysis of main directions which the major international consulting groups are considering as an direct impact of pandemic.  The first part of the paper provides a structured overview about the chosen analysis framework, while research results and recommendations, with highlights and lowlights from existing surveills, form the conclusions and last part. Last 2020 year represented a business turning point on global supply chains and consequently required new approaches and vital cooperation for its strengthening.
Keywords: Supply Chains; Global Supply Chains; Power Energy Sector; Pandemic